Ischaemum dioecum (Poaceae: Andropogoneae): the most strangest new species from Northern Western Ghats, Maharashtra, India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2022)
Ischaemum dioecum, a new strange species from Northern Western Ghats, Maharashtra, India is described and illustrated. The most spectacular and unusual feature of the species is its dioecious breeding system i.e. male and female plants are sexually separate entities, which is being documented first time in the tribe Andropogoneae. Other distinguishing features are such as: sessile spikelets 1-flowered (only upper floret developed), palea bi-dentate with an arista from the sinus and pedicelled spikelet reduced or absent; stamens four with unusually filiform and elongated filaments, ca. 15 mm long; peduncle of male plants glandular and with tubercle-based bristles; style and stigma extraordinarily long each may be up to 14 mm long and pedicel 1/2–4/5 of the sessile spikelet. A table of morphological comparison and detailed discussion with allied species from Africa, India and Australia is given along with the keys to close genera. A detailed discussion on the similar case of dioecism in grasses; habitat characteristics, distribution of the populations and inter-specific interaction, adaptation and morphological affinities of I. dioecum is discussed with African, Indian and Australian taxa. It is apparently a narrow endemic species. Based on IUCN Red List Categories and Criteria, the species is assessed here as Critically Endangered (CR).